A Review on Aerobic Biological Processes for Palm Oil Mill Effluent: Possible Approaches - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus; A. A., Azoddein (IOP Publishing, 2020)
On large scale, many countries like Indonesia and Malaysia receive economic advantage from employing numerous mills to produce and sell palm oil. Despite the benefits, contaminated effluents from palm oil processing have polluted enormous quantities of fresh water, which leads to massive scarcity of fresh water. Moreover, vast quantities of fresh water with steady rainfalls were placed in a country known as Malaysia, but currently, it has massive fresh water wastage because of environmental pollution, and discharging unwell treated palm oil mill effluent (POME). Also, the increasing amounts of POME suffocate agriculture, fresh water, aquatic life, and human health and results in a fantastic medium for bacteria, viruses, and diseases growth. Therefore, palm oil mill effluent receives huge attention since treatment technologies are highly cost, which forces palm oil industries to reuse wastewater in several needs and conserve the available fresh water. Presently, palm oil industries are looking for treatments with low costs, low energy consumptions, and good performance to boost a greener image of palm oil production. This review shows and summarizes most of the possible approaches of aerobic biological treatments to decompose POME, showing their advantages and disadvantages. Finally, this review finds developing a hybrid system comprised from number of aerobic biological treatments can defeat stand-alone technology limitations and improve effluent quality.